Combining magnetic particle imaging and magnetic fluid hyperthermia for localized and image-guided treatment. (15th December 2020) - Lu, Yao; Rivera-Rodriguez, Angelie; Tay, Zhi Wei; Hensley, Daniel; Fung, K.L. Barry; Colson, Caylin; Saayujya, Chinmoy; Huynh, Quincy; Kabuli, Leyla; Fellows, Benjamin; Chandrasekharan, Prashant; Rinaldi, Carlos; et al.
Abstract: Magnetic fluid hyperthermia (MFH) has been widely investigated as a treatment tool for cancer and other diseases. However, focusing traditional MFH to a tumor deep in the body is not feasible because the in vivo wavelength of 300 kHz very low frequency (VLF) excitation fields is longer than 100 m. Recently we demonstrated that millimeter-precision localized heating can be achieved by combining magnetic particle imaging (MPI) with MFH. In principle, real-time MPI imaging can also guide the location and dosing of MFH treatments. Hence, the combination of MPI imaging plus real time localized MPI–MFH could soon permit closed-loop high-resolution hyperthermia treatment. In this review, we will discuss the fundamentals of localized MFH (e.g. physics and biosafety limitations), hardware implementation, MPI real-time guidance, and new research directions on MPI–MFH. We will also discuss how the scale up to human-sized MPI–MFH scanners could proceed.